The interaction effect of independent boards on corporate governance-corporate social responsibility (CG-CSR) and performance nexus - Ismail, Rusmawati; Abdul Manab, Norlida; Karim, Sitara (Asian Academy of Management & Penerbit Universiti Sains Malaysia, 2020)
The financial crises over the past two decades were identified as the main reason for the economic collapse. Malaysia suffered the same fate when many organisations crumpled from inappropriate compliance of governance mechanisms and corporate social responsibility (CSR) disclosure practices. Given this condition, this study intends to examine the effects of governance mechanisms and CSR practice on firm performance and the moderating effect of board independence is investigated on corporate governance-CSR (CG-CSR) and performance nexus of 588 Malaysian companies listed on Bursa Malaysia between 2006 and 2017. Both accounting-based (ROA) and market-based (Tobin’s Q) performance measures have been used for measuring performance. Dynamic model using Generalized Method of Moments (GMM) has been employed on the dataset to control for potential endogeneity, reverse causality, and dynamic heterogeneity. Findings indicate that ownership concentration negatively affects ROA; chief executive officer (CEO) duality positively affects ROA and negatively affects Tobin’s Q. Moreover, investment on CSR is negatively related to both performance measures. Finally, board independence negatively moderates the CG mechanisms, CSR practice, and performance relationship. Findings of the study have implications for Bursa Malaysia and Securities Commission Malaysia to reset the limit of independent directors on board so that their unnecessary interference in operations of management may be avoided. Furthermore, companies need to reassess their CSR strategies whether they are spending on CSR activities or hiding their financial malfeasance in the name of investment on CSR.